A New Formulation Based on Ozonated Sunflower Seed Oil: In Vitro Antibacterial and Safety Evaluation. (4th May 2017) - Serio, Francesca; Pizzolante, Graziano; Cozzolino, Giuseppe; D'Alba, Maria; Bagordo, Francesco; De Giorgi, Mattia; Grassi, Tiziana; Idolo, Adele; Guido, Marcello; De Donno, Antonella
ABSTRACT: The objective of this study was to investigate the potential in vitro biological properties of Oz.Or.Oil 30, a new formulation composed of 30% ozonated sunflower seed oil, which is believed to keep skin smooth and moisturized, supporting repair processes, tissue regeneration and re-epithelialization of wounds. The antibacterial activity, the qualitative and quantitative evaluation of the cytotoxic effect of the formulation on cultures of Vero cells and 3T3 fibroblasts showed that Oz.Or.Oil 30 merits further in vivo study using clinical-laboratory correlations, because it could be suggested as an alternative therapy against bacterial and fungal diseases.